Alcohol use and sexual risk behaviour among men and women in inner-city Johannesburg, South Africa - Braimoh Bello; Harry Moultrie; Aleefia Somji; Matthew F. Chersich; Charlotte Watts; Sinead Delany-Moretlwe (BMC, 2017)
Abstract Background Alcohol misuse is a key factor underlying the remarkable vulnerability to HIV infection among men and women in sub-Saharan Africa, especially within urban settings. Its effects, however, vary by type of drinking, population group and are modified by socio-cultural co-factors. Methods We interviewed a random sample of 1465 men living in single-sex hostels and 1008 women in adjacent informal settlements in inner-city, Johannesburg, South Africa. Being drunk in the past week was used as an indicator of heavy episodic drinking, and frequency of drinking and number of alcohol units/week used as measures of volume. Associations between dimensions of alcohol use (current drinking, volume of alcohol consumed and heavy episodic drinking patterns) and sexual behaviours were assessed using multivariate logistic regression. Results Most participants were internal migrants from KwaZulu Natal province. About half of men were current drinkers, as were 13% of women. Of current male drinkers, 18% drank daily and 23% were drunk in the past week (women: 14% and 29% respectively). Among men, associations between heavy episodic drinking and sexual behaviour were especially pronounced. Compared with non-drinkers, episodic ones were 2.6 fold more likely to have transactional sex (95%CI = 1.7-4.1) and 2.2 fold more likely to have a concurrent partner (95%CI = 1.5-3.2). Alcohol use in men, regardless of measure, was strongly associated with having used physical force to have sex. Overall effects of alcohol on sexual behaviour were larger in women than men, and associations were detected between all alcohol measures in women, and concurrency, transactional sex and having been forced to have sex. Conclusions Alcohol use and sexual behaviours are strongly linked among male and female migrant populations in inner-city Johannesburg. More rigorous interventions at both local and macro level are needed to alleviate alcohol harms and mitigate the alcohol-HIV nexus, especially among already vulnerable groups. These should target the specific dimensions of alcohol use that are harmful, assist women who drink to do so more safely and address the linkages between alcohol and sexual violence.